Development of Android-Based Learning Style Information System at SMK Muhammadiyah 1 Wates - Shafyanta, Zulfa Kurniawan (Institute of Computer Science (IOCS), 2023)
This study aims to (1) develop an android-based learning style information system to identify and provide information on student learning styles in each class, (2) determine the quality of software developed based on ISO/IEC 25010 software quality testing standards on aspects of functional suitability , compatibility and usability. The method used in this study is Research and Development using the Rational Unified Process (RUP) software development procedure which consists of 4 stages, namely inception, elaboration, construction and transition. The results of this study are 1) an android-based learning style information system for know and provide information on the learning styles of students in each class. To find out the learning styles of students, the system developed uses the VAK Learning Styles Questionnaire from Sarah (2015), 2) the results of software testing using quality standards ISO/IEC 25010 on aspects (1) functional suitability get the results of all functions of the software developed can run 100%,